Improvisation and the composed score: a consideration of spontaneous and predetermined compositional processes in the production of screen music - Sher, Daniel Moshe (My University, 2020)
Improvisation has been and continues to be an ever-present factor in screen music production. This dissertation, made up of a portfolio of work for screen and a written thesis, explores the multiple and complex roles improvisation plays in the production of music for screen. The research questions–how improvisation informs predetermined music, and how predetermined musical material, structural harmonic forms or thematic ideas are used as the basis for improvisation–are explored through a combination of methodologies: examining case studies of specific films and scores, conducting interviews with musicians and composers (chiefly with Philip Cox, Mychael Danna and Carlo Mombelli), composing and improvising a portfolio of works for screen, and auto-ethnography where I reflected on my experiences in the creation of my portfolio. Creative processes employed by screen composers –such as the development of musical material or the collaboration between composers and performing musicians–are scrutinised in this written thesis, and the ways in which improvised and reworked scores have different effects on the artform and its reception are explored. Ultimately, scores sound quite different depending on how much of an improvised sound is employed –whether it is a worked-upon or spontaneous-sounding score. The research project aims to benefit screen composers who wish to better understand the compositional process by implementing the methodologies extrapolated from those of past and current composers. It also aims to benefit filmmakers, as the dynamics of the relationships between composers, editors, directors and other contributors to the creation of screen music are redefined and clarified
A thesis submitted to the Wits School of Arts, Faculty of Humanities, University of the Witwatersrand in partial fulfilment of the requirements for the degree of Master of Music, Johannesburg 2020